Artificial neural network based arcing fault detection algorithm for underground distribution cable - Chan, Wei Kian; Zin, Abdullah Asuhaimi Mohd; Ahmad, Hussein; Majid, Md. Shah; Muda, Zaniah; Lo, Kwok Lun (Penerbit Universiti Sains Malaysia, 2004)
Arcing fault occurs in underground distribution cable due to electrical and water treeing in XLPE insulation and inadequate splices assembly. These faults can cause considerable damage to the equipments if they are not detected and isolated promptly